MODERN VIEWS ON A PROBLEM OF CONSTIPATION IN CHILDREN - A POSITION OF PEDIATRICIANS - F.Ch. Shakhtakhtinskaya (Union of pediatricians of Russia, 2009)
This article highlights the issues of definition and classification of chronic constipation, the most prevailing pathology among gastrointestinal tract diseases. The authors demonstrate anatomical and physiological specifics of children's gastrointestinal tract, pathogenic aspects of this condition development. Also this article covers modern principles of dietary treatment and pharmacotherapy of constipation in children.Key words: chronic constipation, pathogenesis, clinical aspects, diagnostics, treatment, children.